A New AMHS Testbed for Semiconductor Manufacturing - Lee, Kwanwoo; Song, Siyong; Chang, Daesoon; Park, Sangchul (Proceedings - Winter Simulation Conference, 2022)
This paper proposes a new dataset of semiconductor fab simulation models. As the size and complexity of FABs increase, it is essential to operate automated material handling systems (AMHS) efficiently. Although the latest testbed, SMT2020 (Semiconductor Manufacturing Testbed2020), is realistic in scale and complexity for modern semiconductor FABs, there is a lack of details on AMHSs. Therefore, we developed details for an AMHS simulation model with sufficient scale and complexity. A full description of the simulation model features is provided, compared with an assumption about transport times in SMT2020. This study aims to provide a test environment for researchers to test operation and logistics in a semiconductor FAB. The prototype of the proposed testbed is open to public use.
Keywords: A: semiconductors; Automated material handling systems; Modeling features; Semiconductor fab simulation; Semiconductor manufacturing; Simulation model; System simulation models; Test Environment; Test operations; Transport time